3-Aminopropyltrimethoxysilane Functionalized Mesoporous Materials and Uptake of Metal Ions - A. Alothman, Zeid; W. Apblett, Allen (Asian Journal of Chemistry, 2010)
γ-Aminopropyl-functionalized mesoporous materials were synthesized by chemical modifcation of a HCl-ethanol washed mesoporous silica (OSU-6-W) with 3-aminopropyltri-methoxysilane (APTMS). The synthesized inorganic-organic hybrids were characterized by solid state 29Si NMR spectroscopy, a titration method and elemental analysis of the modified samples. The average numbers of pendant groups were found to be 2.47 and 4.71 groups/nm2. Surface area analysis showed that these materials have channel diameters of 43.6 and 36.2 Å and surface areas of 1023 and 709 m2/g. Infrared spectroscopy, solid state NMR for 13C and 29Si nuclei and X-ray diffraction patterns are in agreement with the success of the preparation of organicallymodified mesoporous silicas. Adsorption experiments of Cu2+, Zn2+ and Cd2+ shows a remarkably high adsorption capacities with an increase in the surface density of amino groups and affected by the pH of the medium, surface areas and pore sizes.